Sistema experto probabilístico para el diagnóstico de infecciones respiratorias agudas en el Hospital Provincial De Bolívar - Villanueva León, Sergio Anselmo (2018)
This thesis deals with the development of a probabilistic expert system for the_x000D_ diagnosis of Acute Respiratory Infections, which will be used in the area of medicine_x000D_ of the Provincial Hospital of Bolívar and will serve as a support tool to the_x000D_ doctor and/or nursing technician to take an accurate decision, allowing for this to_x000D_ make an opportune diagnosis of the patient’s illness._x000D_ In addition, the knowledge acquisition process for the probabilistic expert system_x000D_ is specified, modeled through its three levels of the CommonKADS methodology_x000D_ and integrating the Bayes theorem for the probabilistic calculation._x000D_ Where was obtained as a result after making the corresponding tests that the expert_x000D_ system has an accuracy index of 85 %; what is considered a satisfactory result, as_x000D_ well as the response time was reduced to an interval of 4 to 7 minutes per query